2020
DOI: 10.1002/joc.6912
|View full text |Cite
|
Sign up to set email alerts
|

Variations in northeast Asian summer precipitation driven by the Atlantic multidecadal oscillation

Abstract: By analysing a 113–year (1900–2012) observational dataset, it is shown that the interdecadal fluctuation of the summer precipitation over Northeast Asia differs from that in central East Asia during the 20th century, and has experienced three interdecadal shifts in the 1920s, mid‐1960s and late 1990s. That fluctuation coincides well with the multidecadal fluctuation of the sea surface temperature in the North Atlantic, known as the Atlantic Multidecadal Oscillation (AMO). The AMO affects Northeast Asia via a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 52 publications
1
12
0
Order By: Relevance
“…(2016) identified interdecadal changes in the dominant east–west and north–south spatial patterns responsible for the interannual variation in summer precipitation. Furthermore, recent studies suggested that the fluctuation of summer precipitation over Siberia and northeast China coincides well with the multidecadal fluctuation of sea surface temperature (SST) in the North Atlantic, which is known as the Atlantic Multidecadal Oscillation (AMO; Sun et al ., 2015; Piao et al ., 2020; Si et al ., 2020). The north–south dipole pattern, which increases (decreases) precipitation in eastern Siberia (northeast China), was dominant when the AMO index was positive after the mid‐1990s (Piao et al ., 2020; Sun et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…(2016) identified interdecadal changes in the dominant east–west and north–south spatial patterns responsible for the interannual variation in summer precipitation. Furthermore, recent studies suggested that the fluctuation of summer precipitation over Siberia and northeast China coincides well with the multidecadal fluctuation of sea surface temperature (SST) in the North Atlantic, which is known as the Atlantic Multidecadal Oscillation (AMO; Sun et al ., 2015; Piao et al ., 2020; Si et al ., 2020). The north–south dipole pattern, which increases (decreases) precipitation in eastern Siberia (northeast China), was dominant when the AMO index was positive after the mid‐1990s (Piao et al ., 2020; Sun et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The AMO can modulate summer rainfall and circulation over NEA through the mid‐latitude wave train. The close relationship between the AMO and the mid‐latitude wave train has also been reported in previous studies (Lin et al ., 2016; Wu et al ., 2016; Hong et al ., 2017; Wang et al ., 2017b; Hong et al ., 2018; Shi et al ., 2019; Si et al ., 2021). In addition to suppressed rainfall, Hong et al .…”
Section: Discussionmentioning
confidence: 99%
“…As an important driving factor of climate change, the Atlantic Multidecadal Oscillation (AMO) strongly influenced climate variability over the world (Li et al ., 2009; Wang et al ., 2017) including China (Zhang et al ., 2020). The linkages of AMO and Northeast Asia are related to the teleconnection extending from the North Atlantic to North America (Si et al ., 2021). The positive phase of the AMO could increase the summer precipitation in Northeast Asia through enhancing the East Asian summer monsoon (Zhang et al ., 2020; Si et al ., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The linkages of AMO and Northeast Asia are related to the teleconnection extending from the North Atlantic to North America (Si et al ., 2021). The positive phase of the AMO could increase the summer precipitation in Northeast Asia through enhancing the East Asian summer monsoon (Zhang et al ., 2020; Si et al ., 2021). The periodic signals of 72.99a and 78.74a in our reconstructed streamflow are in the range of 65a–80a fluctuation of the AMO, indicating the impact of AMO on the long‐term hydroclimatical variability over the Weihe River basin (Figure 9).…”
Section: Discussionmentioning
confidence: 99%